Design thinking: A creative approach to educational problems of practice. (December 2017) - Henriksen, Danah; Richardson, Carmen; Mehta, Rohit
Abstract: The problems educators face in professional practice are complex, varied, and difficult to address. These issues range across teaching and learning topics, to social or community issues, classroom climate issues and countless others. Such problems are multifaceted, cross-disciplinary, human-centered, and rarely solved through simple or linear solutions. Grappling with them requires educators to think creatively about educational problems of practice. But given the challenges and expectations facing teachers, creativity is often seen as leisure in teaching practice. While creativity is considered a core 21st century thinking skill, many people are hesitant to self-identify as "creative, " or are uncomfortable with intellectual risk-taking and open-endedness. We suggest that design thinking may provide an accessible structure for teachers and teacher educators to think creatively in dealing with educational problems of practice. We examine a qualitative study of a graduate teaching course framed around using design thinking to creatively approach educational problems of practice. We discuss thematic takeaways that teachers experienced in learning about and using design thinking skills to approach educational problems of practice. Implications suggest that design thinking skills may provide habits of mind that benefit teachers in creative problem navigating.